Peripheral blood T-cell modulation by omalizumab in chronic urticaria patients - López, Cristina; Depreux, Nathalie; Bielsa, Isabel; Roger, Albert; Quirant-Sanchez, Bibiana; Basagaña, Maria; Jurgens, Yanina; Padró, Clara; Miquel, Sira; Martinez-Caceres, Eva; Teniente-Serra, Aina (Frontiers in Immunology, 2024)
Abstract Background: Chronic spontaneous urticaria (CSU) is a highly prevalent and difficult to manage cutaneous disease characterized by the presence of recurrent urticaria, angioedema, or both, for a period of six weeks or longer. One of the biological treatments used for patients with CSU with an autoimmune background and bad control of the disease is omalizumab, an anti-IgE monoclonal antibody. The understanding of the mechanism of action of this biological drug in CSU along with the identification of potential biomarkers of clinical response, can be helpful in the personalised management of the disease. Objective: To analise the effect of omalizumab on peripheral blood lymphocyte subpopulations in patients with CSU, in order to identify potential biomarkers of treatment response. Methods: We analysed 71 patients with CSU [33 under omalizumab and 38 under non-immunomodulatory drugs (treated with antihistamines; NID)], and 50 healthy controls. An exhaustive immunophenotyping of whole blood T-cell subpopulations, including naïve, central memory, effector memory, effector cells, Th1, Th2 and Th17 was performed by multiparametric flow cytometry. Moreover, in CSU patients we analysed markers of inflammation (ESR, DD, CRP), atopy (prick test, IgE quantification), and autoimmunity (anti-thyroid antibodies and indirect basophil activation test).To evaluate the clinical activity, the Urticaria Activity Score 7 (UAS 7) test was used. Results: In patients with CSU under treatment with omalizumab there was a significant decrease the percentage of naïve and an increase in the percentage of central memory CD4 T cells as well as a decrease in the percentage of naïve and increase in the percentage of effector CD8 T cell subsets. Moreover, patients under treatment with omalizumab had higher percentages of Th1 and Th2 cells than patients under treatment with NID. Conclusions: The immune monitoring of T-cell subpopulations in patients with CSU starting omalizumab, may be a useful strategy to analyse treatment response in the clinical practice.